Effect of Aerobic Exercise Training on Circulating s-Klotho in a Heart Transplant Recipient; A Case Report - Exford, T. J.; Saghiv, Moran; Goldhammer, Ehud; Ben-Sira, David; Sagiv, Michael (British Journal of Healthcare and Medical Research, 2023)
Reduced circulating s-Klotho has been seen in heart failure patients, However, its values are increased following aerobic exercise training. The purpose of the case study was to examine whether high intensity aerobic exercise training increase serum s-Klotho levels in untrained heart transplant recipient, and to examine the relation between plasma s-Klotho concentration and peak oxygen uptake (VO2peak). Methods: Untrained heart recipient 25 years old trained for 60 min-1×4 times×wk-1 for 12 wks-1 at 85% of VO2peak. Testing sessions were performed at 0, and 12 weeks. Blood samples were analyzed for s-Klotho by an ELISA kit. Results: Subject increased its VO2peak from 25.1 to 31.2 mL×kg-1×min-1, s-Klotho increased from 349 to 467 pg×mL-1. Conclusions: This case report indicated that aerobic exercise was tolerated without any difficulties, along with significantly improve in s-Klotho and peak oxygen uptake values. In addition, it is apparent that training at 85% work capacity in young heart transplant recipients following heart failure benefits to reestablish functional of central oxygen delivery variables mainly; cardiac output. Thus, it may have a better prognosis for the entire heart transplant recipient's population.